Development of a records and archives management program for the University of the Philippines (UP) School of Urban and Regional Planning (SURP) Library - Manjares, Maggie May I. (2018)
The UP SURP Library is encountering issues on records and archives management, including unsystematic records classification and organization, missing records (i.e. lost, misfiled, and unlocated records), inefficient records and archives access and retrieval, some archives have already been categorized by type but majority are not. Some have not yet been classified, accessioned, cataloged, labeled nor inventoried yet. The library does not have any written tools and manual on records and archives management. This project will fill that gap by developing a records and archives management program (RAMP) for the UP SURP Library. Having RAMP leads to effective delivery of services and efficient office operations because it guides the Library in collecting, assessing, describing, organizing and preserving institutional/community knowledge and history.